Three cases of brain hydatidosis in North Khorasan, Iran. Issue 7 (22nd July 2022) - Shafiei, Reza; Raeghi, Saber; Jafarzadeh, Fatemeh; Najjari, Mohsen; Ghatee, Mohammad Amin; Shokri, Azar
Abstract: Cystic hydatidosis is a serious public health problem in Iran. Although cysts can develop in almost all organs and the brain cysts are very rare. Here, we present 3 confirmed cases of brain hydatidosis and the patients who underwent successful surgery. Pathological examinations demonstrated the presence of cystic hydatidosis. Abstract : Hydatidosis should be considered a differential diagnosis of any cyst in the brain particularly in endemic regions including Iran.